Understanding the Influence of Cyberbullying Among High School Students in Philippine Public Schools in the Post-Pandemic Era - Buguina, Lydia A.; Buguina, Emil Constantine (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This research sought to explore the effects of cyberbullying on high school students attending public schools in the Philippines. Given the widespread use of digital communication platforms and social media, cyberbullying has emerged as a significant societal concern. The study aims to determine the perceptions of senior high school students in the concept of bullying in the post pandemic era. The participants in this study consisted of 41 Grade 12 students from a public high school in the Philippines. Simple random sampling technique was used to select students which formed the research population. The study reveals that a significant number of SHS students possess knowledge about cyberbullying and its consequences. Among the coping strategies employed by these students include confiding with friends, emerges as a vital source of support in combating cyberbullying. Moreover, the collaboration between parents, students, and the school, along with the involvement of mental health professionals, enables effective communication and provision of assistance to students affected by cyberbullying. It is crucial for schools, teachers, parents, and students to increase their internet posting awareness and understanding of cyberbullying, while students should prioritize treating others kindly online and reporting cyberbullying. Parents should engage in open conversations and monitor their children’s digital activities while teachers and principals must foster a safe environment through education, anti-cyberbullying policies, and victim support.